(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The feeling of «shame» of Chekhov’s characters does not always coincide with the one which author means. Characters in Chekhov’s stories have different reasons for the feeling. They also experience it with different intensity levels. Lexis for the concept of «shame» is rarely verbalized in the text, this emotional state is conveyed by external evidence, behaviour, perception of an environment. Besides, the author distinguishes shame from awkwardness and a state of confusion, that is why lexis which denotes the concept of «shame» is not a synonymic one, as it is always broadly interpreted. In a number of Chekhov’s characters painful feeling of shame awakes conscience, leads to the insight and broader views on a situation and himself. In Chekhov’s stories, as in ones of his classic forerunners, only a person gifted with a moral feeling can experience shame. However, before Chekhov’s works the concept of shame was not such a characteristic feature, but in his stories presence of this feeling as well as its absence is of a great importance for the character. In Chekhov’s stories the concept of «shame» correlates not with the idea of «recovery of a lost person», original sin, or idea of one’s duty, but with the idea of right or wrong overviews, feelings and acts of a character and a society. Key words: Chekhov, character, shame, conscience, truth, feeling, reason, state. DOI 10.18522/1995-0640-2020-2-36-42